2004
DOI: 10.1111/j.1365-2141.2004.05028.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular presentation of primary central nervous system lymphoma: diagnosis and treatment

Abstract: SummaryPrimary ocular lymphoma (POL), a lymphoma of the globe, is a restricted form of primary central nervous system lymphoma (PCNSL) that often progresses to the brain and meninges; frequently it is misdiagnosed until central nervous system (CNS) lymphoma develops. The optimal treatment has not yet been identified. We retrospectively reviewed the course and the treatment of POL in 31 patients. Seventeen patients were treated for isolated POL (group A) and 14 were treated only after CNS disease was diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 34 publications
4
96
0
3
Order By: Relevance
“…In the three larger (n>10) series the outcome of IOL+ patients was comparable to that of IOL-and superior to that in the present study with median PFS of 18 months 2 and median OS of 20-31 months 2,7,18 . This cannot be explained by differences in patients` age or performance status between those analyses and the present study.…”
Section: Discussionsupporting
confidence: 60%
“…In the three larger (n>10) series the outcome of IOL+ patients was comparable to that of IOL-and superior to that in the present study with median PFS of 18 months 2 and median OS of 20-31 months 2,7,18 . This cannot be explained by differences in patients` age or performance status between those analyses and the present study.…”
Section: Discussionsupporting
confidence: 60%
“…However, available data are scarce and based only on retrospec- www.TheOncologist.com tive studies. In a single-center experience, Hormigo et al [121] suggested that patients whose ocular disease was identified and treated before CNS progression had a significantly longer survival time than those who were treated only after CNS disease was diagnosed. Treatment may be focal, including ocular RT and intraocular MTX chemotherapy, or extensive, including systemic chemotherapy and WBRT.…”
Section: Primary Intraocular Lymphomamentioning
confidence: 99%
“…PIOL is a unique malignant lymphoproliferation because of its affectation of an immune privileged site, involving the subretinal pigment epithelium (RPE), retina, vitreous, and optic nerve. Frequently masquerading as a uveitis, PIOL is often misdiagnosed for intraocular inflammation and is treated with corticosteroids [5] or, infrequently, PIOL can masquerade as a viral retinitis and is treated with antiviral medication [6]. It is not until the presumed uveitis fails to respond to corticosteroid therapy that another cause is sought.…”
Section: Introductionmentioning
confidence: 99%